Are Oaks Locally Adapted to Serpentine Soils? - Branco, Sara (Northeastern Naturalist, 2009)
Serpentine soils are extreme habitats known to be involved in processes of local adaptation and speciation of plants. Here I use a greenhouse reciprocal-transplant experiment to compile baseline data for describing patterns of serpentine local adaptation in Quercus ilex subsp. ballota (Holm Oak). I also tested the role of mycorrhizal fungi on the establishment and growth of seedlings on serpentine and non-serpentine soil. Non-serpentine seedlings grew more than serpentine seedlings in all treatments. Plants grew more on non-serpentine soil and mycorrhizal fungi positively influenced seedling growth. I did not find evidence of better seedling performance in their home environment, suggesting the absence of local adaptation. However, I document significant growth differences between serpentine and non-serpentine seedlings, which suggest physiological differences between seedlings from these two soil origins.
doi: 10.1656/045.016.0524doi: 10.1656/045.016.0524The following values have no corresponding Zotero field: publisher: Eagle Hill Institute
Keywords: Mycorrhizal fungi; seedling growth (PG); serpentine

Are Oaks Locally Adapted to Serpentine Soils? (Northeastern Naturalist, 2009)
Serpentine soils are extreme habitats known to be involved in processes of local adaptation and speciation of plants. Here I use a greenhouse reciprocal-transplant experiment to compile baseline data for describing patterns of serpentine local adaptation in Quercus ilex subsp. ballota (Holm Oak). I also tested the role of mycorrhizal fungi on the establishment and growth of seedlings on serpentine and non-serpentine soil. Non-serpentine seedlings grew more than serpentine seedlings in all treatments. Plants grew more on non-serpentine soil and mycorrhizal fungi positively influenced seedling growth. I did not find evidence of better seedling performance in their home environment, suggesting the absence of local adaptation. However, I document significant growth differences between serpentine and non-serpentine seedlings, which suggest physiological differences between seedlings from these two soil origins.
doi: 10.1656/045.016.0524